Kubios threshold-based artefact correction affects heart rate variability parameters in elite athletes - Itaborahy, A.; Freire, R.; Hausen, M. (Journal of Science in Sport and Exercise, 2024)
Purpose Kubios is an intuitive software intended to provide heart rate variability (HRV) processing. It is widely used to assess athletes` readiness for new training sessions and autonomic balance responses to the training programme. However, Kubios` filtering levels` effect on artefact correction for elite athletes is still unclear. This study aims to assess the impact of different Kubios threshold-based artefact correction levels on the HRV-derived parameters in male and female elite athletes.